Improving transmission delay with sink location in low-duty-cycle wireless sensor networks. (2017) - Lin, Yu-Yuan; Ssu, Kuo-Feng
A low-duty-cycle approach can significantly reduce the energy consumption in wireless sensor networks (WSNs). Sensors stay dormant most of the time and wake up only when performing tasks. However, such a technique, while prolonging the network lifetime, sets excessive challenges for reducing the transmission delay. The dissemination at different locations of the sink node results in various E2E delays because of the different transmission sequences corresponding to the working schedules of relay nodes. Thus, determining a suitable location for the sink node can efficiently improve the E2E delay. In this paper, a geographic cluster-based sink location determining (GCSLD) algorithm is introduced to reduce the transmission latency in low-duty-cycle WSNs by searching for an appropriate location for the sink node. The GCSLD algorithm is implemented and evaluated successfully. The simulation results confirm that the GCSLD determines suitable locations with lower execution overhead.